Diversity and species composition of microbiota associated with dengue mosquito breeding habitats: A cross-sectional study from selected areas in Udapalatha MOH division, Sri Lanka - Yashoda Kumari; Deepika Amarasinghe; Koshila Ranasinghe (Asian Pacific Journal of Tropical Medicine, 2023)
Objective: To determine the diversity of microbiota associated with different breeding habitats of dengue vector mosquitoes Aedes (Ae.) aegypti and Ae. albopictus and to identify any parasitic, epibiont, pathogenic, competitive or predatory species. Methods: Sampling was performed from a variety of breeding habitats using dipping, pipetting and siphoning techniques. Microbiota in water samples were preserved using Rose Bengal solution and Lugol’s iodine, and were identified. Live samples of microbiota were kept under laboratory conditions to observe any pathogenic or parasitic microbiota interacting with larvae. Results: A total of eleven microbiota species (Canthocamptus staphylinus, Canthocamptus microstaphylinus, Parastenocaris brevipes, Lepadella ovalis, Lepadella patella, Rotatoria rotatoria, Rotatoria macrura, Asplanchna brightwelli, Trichocerca rattus, Euglena variabilis, and Flagilaria capucina) belonging to four (4) phyla (Arthropoda, Rotifera, Euglenozoa, and Ochrophyta) and 8 microbiota species belonged to four phyla (Arthropoda, Rotifera, Euglenozoa, and Ochrophyta) were identified from Ae. aegypti and Ae. albopictus breeding habitats respectively. There was a higher percentage (54.54%) of larval habitats positive for the secondary vector Ae. albopictus than through the primary vector Ae. aegypti in the Gampola urban area indicating higher possibility of transmitting the dengue virus through the secondary vector. However, no pathogenic or parasitic ciliates on mosquito larvae were encountered in the present study. Those findings may be due to sampling maingly from temporary container-type breeding habitats. Conclusions: The relative distribution of microbiota associated with mosquito species differed significantly among Ae. aegypti and Ae. albopictus. The overall findings of this study could help in implementing novel eco-friendly vector-control strategies in the study area.